Orta Enlem İyonküresi Difüzyon Katsayılarının Değişimi ve F10.7 Güneş Akısı ile İlişkisinin İncelenmesi - Sağır, Selçuk (Fırat University, 2017)
İyonkürenin F2 bölgesinde elektron yoğunluğunun maksimum olduğu yükseklikte(hmF2) elektron için elde edilen difüzyon katsayıları matris elemanlarının ekinoks ve gündönümü günleri için yerel zaman ve yükseklik ile değişimleri Ankara/Türkiye koordinatları için hesaplandı. Ayrıca 240 km yükseklikte elde edilen difüzyon katsayı matrisinin tüm elemanları ile en yaygın kullanılan Güneş indisi- F10.7 Güneş akısı- arasındaki ilişki incelendi. İncelemenin sonucu olarak katsayılar matrisinin Dxx elamanı en küçük, Dzz elamanı ise en büyük değeri aldığı gözlendi. Ekinoks ayları için difüzyon katsayılarının günlük değişimlerindeki maksimum değer ile minimum değer arasındaki fark, gün dönümlerindekinden daha büyük olduğu görüldü. F10.7 Güneş akısı ile difüzyon matrisinin tüm elamanları arasında yaklaşık aynı oranda negatif bir ilişki belirlendi.

The changes in local time and altitude of the matrix elements of diffusion coefficients obtained for electron at the maximum electron density height (hmF2) in F2 region of the ionosphere are calculated on the equinox and solstice days for the Ankara / Turkey coordinates. Furthermore, the relationship between the most commonly used solar indices- F10.7 solar flux- and all elements of the diffusion coefficient matrix obtained at 240 km height is investigated. As a result of the examination, it is seen that element of Dxx of the coefficients matrix has the smallest and the element of Dzz has the greatest value. For the equinox months, it is seen that the difference between the maximum value and the minimum value in the daily variations of the diffusion coefficients is greater than in the solstices. A negative relationship at the same rate has nearly been determined between the F10.7 solar flux and all elements of the diffusion matrix.
The change of Diffusion Coefficients of Middle Latitude Ionosphere and Investigation of Relation to F10.7 Solar Flux